Inhibition of Thrombin Generation in Plasma by Inhibitors of Factor Xa - Prasa, D; Svendsen, L; Stürzebecher, J (Thrombosis and Haemostasis, 1997)
A series of inhibitors of factor Xa (FXa) were investigated using the thrombin generation assay to evaluate the potency and specificity needed to efficiently block thrombin generation in activated human plasma. By inhibiting FXa the generation of thrombin in plasma is delayed and decreased. Inhibitor concentrations which cause 50 percent inhibition of thrombin generation (IC50) correlate in principle with the Ki values for inhibition of free FXa. Recombinant tick anticoagulant peptide (r-TAP) is able to inhibit thrombin generation with considerably low IC50 values of 49 nM and 37 nM for extrinsic and intrinsic activation, respectively. However, the potent synthetic, low molecular weight inhibitors of FXa (Ki values of about 20 nM) are less effective in inhibiting the generation of thrombin with IC50 values at micromolar concentrations.The overall effect of inhibitors of FXa in the thrombin generation assay was compared to that of thrombin inhibitors. On the basis of similar Ki values for the inhibition of the respective enzyme, synthetic FXa inhibitors are less effective than thrombin inhibitors. In contrast, the highly potent FXa inhibitor r-TAP causes a stronger reduction of the thrombin activity in plasma than the most potent thrombin inhibitor hirudin.